Determinants of Community on Covid-19 Vaccine Participation in RT 01 RW 05, Ngadiluwih Village Kediri District - lingga Kusuma Wardani; Alfi Aqliana Nur Fahma; Dhita Kurnia Sari; Nuryeny Hidajaturrokhmah; Dedi Saifulah; Retno Palupi Yonni Siwi (Universitas STRADA Indonesia, 2023)
Background: Coronavirus disease 2019 (Covid 19) is an infectious disease that is becoming a global pandemic. The purpose of this study was to analyze the effect of social support and trust on the participation of the Covid-19 vaccine in the community in RT 01 RW 05 Ngadiluwih Village, Kediri Regency. Purpose: The design of this study is an observational quantitative study with a cross sectional approach with the focus of the research directed at analyzing the effect of social support and trust on the participation of the Covid-19 vaccine in the community in RT 01 RW 05 Ngadiluwih Village, Kediri Regency. The total population is 62 respondents and a sample of 54 respondents is taken by using Simple Random Sampling technique. Methods: The findings showed that almost half of the respondents had sufficient social support category as many as 22 respondents (40.74%). Almost half of the respondents have confidence in the medium category as many as 25 respondents (46.30%). Most of the respondents participated in vaccination in the complete category as many as 30 respondents (55.56%). Results: Based on the results of the logistics regression analysis showing that the p-value of 0.001 it was concluded that there was an effect of social support on the participation of the Covid-19 vaccine in the community in RT 01 RW 05 Ngadiluwih Village, Kediri Regency. And the p-value of 0.004 <0.05, H1 is accepted, so it can be concluded that there is an influence of trust on the participation of the Covid-19 vaccine in the community in RT 01 RW 05 Ngadiluwih Village, Kediri Regency. Conclusion: It is hoped that the community can carry out a complete COVID-19 vaccination, both vaccine 1 and vaccine 2, and even attempt to participate in conducting booster vaccines to stop the spread of COVID-19.